2017
DOI: 10.1093/mnras/stx3023
|View full text |Cite
|
Sign up to set email alerts
|

A dearth of small particles in the transiting material around the white dwarf WD 1145+017

Abstract: White dwarf WD 1145+017 is orbited by several clouds of dust, possibly emanating from actively disintegrating bodies. These dust clouds reveal themselves through deep, broad, and evolving transits in the star's light curve. Here, we report two epochs of multi-wavelength photometric observations of WD 1145+017, including several filters in the optical, K s and 4.5 µm bands in 2016 and 2017. The observed transit depths are different at these wavelengths. However, after correcting for excess dust emission at K s … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Both detections of wavelength-dependent transits for WD 1145 (this analysis and Hallakoun et al (2017)) are the only ones so far which included observations in the uband range, where WD 1145 displays many broad absorption lines caused by circumstellar gas. The fact that other studies (Alonso et al 2016;Zhou et al 2016;Croll et al 2017;Izquierdo et al 2018;Xu et al 2018) did not observe wavelengths shorter than 4300Å could explain why they did not detect bluing. As discussed by Hallakoun et al (2017) and Redfield et al (2017), the most plausible explanation for the u -band excess during transits is the reduced circumstellar absorption along the line-of-sight.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Both detections of wavelength-dependent transits for WD 1145 (this analysis and Hallakoun et al (2017)) are the only ones so far which included observations in the uband range, where WD 1145 displays many broad absorption lines caused by circumstellar gas. The fact that other studies (Alonso et al 2016;Zhou et al 2016;Croll et al 2017;Izquierdo et al 2018;Xu et al 2018) did not observe wavelengths shorter than 4300Å could explain why they did not detect bluing. As discussed by Hallakoun et al (2017) and Redfield et al (2017), the most plausible explanation for the u -band excess during transits is the reduced circumstellar absorption along the line-of-sight.…”
Section: Discussionmentioning
confidence: 87%
“…Zhou et al (2016) performed simultaneous observations in the optical and near-infrared, over the wavelength range of 0.5-1.2 µm, with no measurable difference in transit depths for multiple photometric pass-bands, allowing them to place a lower limit of 0.8 µm on the grain size in the putative transiting debris cloud. Xu et al (2018) presented observations in the optical, K s and 4.5 µm bands, and found the same transit depths at all wavelengths from which they conclude that there is a deficit of small particles (with radii 1.5 µm) in the transiting material. Most recently, results from simultaneous fast optical spectrophotometry and broad-band photometry of WD 1145 were published by Izquierdo et al (2018), who found no significant colour differences between five wavelength bands over the wavelength range 4300-9200Å.…”
Section: Wd 1145+017mentioning
confidence: 81%
“…The related scenario of metal accretion onto white dwarfs has now matured into an extremely active field of research around evolved planetary systems (Veras 2016). For a small fraction of these systems it is possible to study the debris disk or gas around the white dwarf (Jura 2003;Farihi et al 2009;Manser et al 2016;Xu et al 2018;Manser et al 2019;Wilson et al 2019) but in most cases the primary evidence is metal pollution from tidally disrupted asteroids in the stellar atmosphere (van Maanen 1917;Zuckerman et al 2003;Gänsicke et al 2012;Vanderburg et al E-mail: t.cunningham@warwick.ac.uk 2015). To transform photospheric metal abundances into the parent body properties requires an accurate model describing the volume of the stellar envelope over which this abundance is prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…They are observed to be common around unevolved stars (Moro-Martín et al 2010;Ballering et al 2017;Anglada et al 2017). Debris discs around white dwarfs have not been directly observed, but their existence is implied by the pollution of their atmospheres by asteroidal material, perhaps from a debris disc that survived stellar evolution (Gänsicke et al 2006;Kilic et al 2006;von Hippel et al 2007;Farihi et al 2009;Jura et al 2009;Farihi et al 2010;Melis et al 2010;Brown et al 2017;Bonsor et al 2017;Xu et al 2018;Smallwood et al 2018b). However, the existence of debris discs around NSs is more uncertain (e.g., Posselt et al 2014).…”
Section: Introductionmentioning
confidence: 99%